Academic-Practice Partnership Builds Innovation and Creative Capacity Following a Human-Centered Design Workshop | OJIN: The Online Journal of Issues in Nursing. - Holt, Jeana M.; Talsma, AkkeNeel; Lloren, Jan Irene C.; Avdeev, Ilya; Eckert, Colleen Lawlor; Mu, Qiyan; Ndakuya-Fitzgerald, Florine; Jastrab, Joann (Online Journal of Issues in Nursing, 2025)
Innovation is the capacity of organizational teams to adapt to environmental changes, generate new value, and integrate it into the system. Human-centered design (HCD) centers on empathy and how people interact with the environment, which helps clinicians understand a problem from the user perspective. Nurses do not usually learn about innovation and HCD skills during their education. A recent solution to remedy this was collaboration between a healthcare system and a university innovation center to facilitate training through an academic-practice partnership. A Midwestern Veterans Health Administration (VHA) partnered with an R1 research university school of nursing and innovation center to co-create an 8-hour HCD workshop. This article reports findings from our mixed method, pre-post design study that evaluated creative self-efficacy, psychological empowerment, and traits of design thinkers of the participants (n = 31). Paired t-tests and linear mixed-effects models indicated statistically significant gains post-intervention at the construct level. Qualitative themes emerging from participant narrative reflections aligned with the constructs and sub-constructs in the instruments and added urgency to apply learnings to their work context. Participant reflections often identified a new sense of creative confidence, HCD skill proficiency, and enthusiasm to share their learnings with colleagues. Nurses creatively solve problems in their daily work; however, most do not learn how to apply HCD methodologies to seek a solution. Academic-practice partnerships can maximize the strengths of strong innovation ecosystems at the university and organizational levels, creating multiple courses of support, resources, and perspectives.